The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/nmd.0000000000001078
|View full text |Cite
|
Sign up to set email alerts
|

Doctor-Diagnosed Arthritis and Self-Reported Physical Health Function Among Middle-Aged and Older Adults With Serious Mental Illness

Abstract: Arthritis is one of the most common chronic conditions in aging adults, with both physical and mental health issues and consequences. However, there is insufficient arthritis research among aging adults with serious mental illness (SMI). This study examined rates of doctor-diagnosed arthritis and its cross-sectional associations with self-reported physical health function among adults aged 50 years and older with SMI. Community-based mental health center participants (n = 176) reported clinical and sociodemogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…Significant associations between loneliness and self-reported health conditions that cause pain were found. This finding is consistent with previous studies that found chronic obstructive pulmonary disorder and arthritis have shown significant negative and adjusted associations with physical health status in people with SMI 35 . Both SMI and chronic pain conditions are conceptualized by biological, psychological, and socio-cultural/environmental models of health and illness 36 .…”
Section: Discussionsupporting
confidence: 93%
“…Significant associations between loneliness and self-reported health conditions that cause pain were found. This finding is consistent with previous studies that found chronic obstructive pulmonary disorder and arthritis have shown significant negative and adjusted associations with physical health status in people with SMI 35 . Both SMI and chronic pain conditions are conceptualized by biological, psychological, and socio-cultural/environmental models of health and illness 36 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, basketball is an aerobic exercise, which can increase the ugly activity of the fetus. With the increase of the amount of basketball exercise, the body fat decomposition speed is accelerated, the utilization rate of fat is improved, the lean weight is increased, and the body fat rate is reduced, which makes the human body more beautiful [5]. Basketball is characterized by long time and high intensity.…”
Section: Influence Of Basketball On Healthmentioning
confidence: 99%
“…The global prevalence of arthritis is ∼0.34% to 0.36% 1–3 . The most common types of arthritis are osteoarthritis (OA), rheumatoid arthritis (RA), psoriatic arthritis (PsA), and gouty arthritis (GA).…”
mentioning
confidence: 99%